Low cost condition assessment method for existing RC bridges. (April 2018) - Stochino, Flavio; Fadda, Maria Luisa; Mistretta, Fausto
Abstract: Aging infrastructures represent a current engineering challenge. Huge budgets are necessary to keep their functionality and the lack of a proper and timely maintenance entails an increasing deterioration and therefore higher repair costs. Therefore, assessing the reliability of infrastructures becomes mandatory, with particular attention to the ones still in service even when their life limit has exceeded. This paper aims to propose a new, fast and low cost method of condition rating for reinforced concrete bridges. This is based on visual inspection and non-destructive testing. The main innovation is represented by the parameters taking into account the mechanical degradation of materials and the damage location at the structural sub-component level. The analysis of some benchmark examples and the comparison with other methods are presented in order to assess the reliability of the new proposal. Highlights: New fast and low cost condition rating method for reinforced concrete bridges Four benchmark cases are presented. Ranking at project level or at network level The method allows one to optimize the maintenance costs.